Influence of the Russia-Ukraine war and COVID-19 pandemic on the efficiency and herding behavior of stock markets: Evidence from G20 nations - Bilal Ahmed Memon; Faheem Aslam; Hafiz Muhammad Naveed; Paulo Ferreira; Omonjon Ganiev (Economies, 2024)
Efficiency in stock markets is essential for economic stability and growth. This study investigates the efficiency and herding behavior of the stock markets from the top economies of the world (known as G20 countries). We classify stock market indices using MSCI classification for the developed and emerging markets to provide a comparative examination using the latest data and by employing the robust multifractal detrended fluctuation (MFDFA) method. In addition to the full sample, the analysis uses sub-sample periods to reveal the hidden features and efficiencies of the G20 markets during the Russia-Ukraine War and COVID-19 for the first time. The findings show the availability of varied multifractality among all G20 stock markets during the overall and crisis periods, exhibit long-range correlations, and may support the fractal market hypothesis. In addition, Italy remains the least efficient, while Germany remains the most efficient stock market. The sub-sample results further reveal unevenness in the local fluctuations and resultant higher inefficiency considering the sheer magnitude and impact of crises on the G20 stock markets. However, the efficiency of developed stock markets performed better as compared to emerging markets. The study of G20 stock markets is useful and provides several implications for a wider audience.
Keywords: F36; G14; G15; N20; O16; P34; 330; COVID-19; efficiency; geopolitical risk; herd behavior; multifractal analysis; war